Discussions on antibiotic therapy and systemic enzyme therapy for pelvic inflammatory disease: A review - Natalia M. Podzolkova; Igor E. Fadeev; Roman E. Kuznetsov; Tatiana N. Poletova (Гинекология)
Pelvic inflammatory disease in women is one of the most important public health problems worldwide. The diagnosis is made based on clinical criteria. Empirical antibiotic therapy is the cornerstone of standard treatment. Antibiotic resistance and associated failures of standard therapy require the search for additional measures beyond those recommended in the clinical guidelines. Systemic enzyme therapy appears to be the most appropriate treatment for improving pelvic inflammatory disease outcomes.